Synergistic Engineering of Heterointerface and Architecture in New‐Type ZnS/Sn Heterostructures In Situ Encapsulated in Nitrogen‐Doped Carbon Toward High‐Efficient Lithium‐Ion Storage. (8th July 2022) - Ke, Chengzhi; Shao, Ruiwen; Zhang, Yinggan; Sun, Zhefei; Qi, Shuo; Zhang, Hehe; Li, Miao; Chen, Zhilin; Wang, Yangsu; Sa, Baisheng; Lin, Haichen; Liu, Haodong; et al.
Abstract: Engineering heterogeneous composite electrodes consisting of multiple active components for meeting various electrochemical and structural demands have proven indispensable for significantly boosting the performance of lithium‐ion batteries (LIBs). Here, a novel design of ZnS/Sn heterostructures with rich phase boundaries concurrently encapsulated into hierarchical interconnected porous nitrogen‐doped carbon frameworks (ZnS/Sn@NPC) working as superior anode for LIBs, is showcased. These ZnS/Sn@NPC heterostructures with abundant heterointerfaces, a unique interconnected porous architecture, as well as a highly conductive N‐doped C matrix can provide plentiful Li + ‐storage active sites, facilitate charge transfer, and reinforce the structural stability. Accordingly, the as‐fabricated ZnS/Sn@NPC anode for LIBs has achieved a high reversible capacity (769 mAh g −1, 150 cycles at 0.1 A g −1 ), high‐rate capability and long cycling stability (600 cycles, 645.3 mAh g −1 at 1 A g −1, 92.3% capacity retention). By integrating in situ/ex situ microscopic and spectroscopic characterizations with theoretical simulations, a multiscale and in‐depth fundamental understanding of underlying reaction mechanisms and origins of enhanced performance of ZnS/Sn@NPC is explicitly elucidated. Furthermore, a full cell assembled with prelithiated ZnS/Sn@NPC anode and LiFePO4 cathode displays superior rate and cycling performance. This work highlights the significance of chemical heterointerface engineering in rationally designing high‐performance electrodes for LIBs. Abstract : A viable anode material composing of new‐type ZnS/Sn heterostructures with rich phase boundaries concurrently encapsulated into hierarchical interconnected porous nitrogen‐doped carbon frameworks (ZnS/Sn@NPC) is developed for high‐performance lithium ion batteries. Its Li + ‐storage mechanism and origins of the superior performance are explicitly elucidated by combining in situ TEM/XRD/Raman studies, a suite of ex situ microscopic and spectroscopic characterizations with theoretical simulations.